Administration of general anaesthesia to a paediatric patient with osteopetrosis - Ozer, Ayse Belin; Erhan, Omer L.; Demirel, Ismail; Ozcan, Sibel (BMJ Publishing Group, 2012)
Osteopetrosis is a rare clinical syndrome characterised by the failure of bone resorption and remodelling, which causes multiple anatomical and physiological impairments. Pathological fractures can occur, in addition to, haemathological and metabolic impairments. Our patient was a 9-year-old girl diagnosed with osteopetrosis in the neonatal period. She had severe anaemia, thrombocytopaenia, hypocalcaemia, as well as growth and development delays. In this case report, the administration of general anaesthesia to the patient for a biopsy of the scalp and skull and a partial maxillectomy is presented. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: ampicillin; calcium; ceftriaxone; hemoglobin; methylprednisolone; metronidazole; potassium; sevoflurane; sodium; Albers Schoenberg disease; anemia; anesthesia induction; article; case report; child; computer assisted tomography; developmental disorder; disease severity; endotracheal intubation; extubation; female; general anesthesia; growth disorder; hematocrit; hospital admission; human; hydrocephalus; hypocalcemia; laboratory test; maxilla resection; operation duration; preoperative evaluation; prescription; priority journal; school child; thrombocyte count; thrombocytopenia; wakefulness